Maceração enzimática da casca residual do despolpamento dos frutos da cajazeira - Vieira, Janaína Maria Martins (2013)
Brazil is one of the countries that most produces organic residues, such as residues of fruit pulp industries, which have contributed to the increased production of organic waste causing serious environmental problems. The Brazilian Northeast stands out due to the huge diversity of fruits considered exotic, where the yellow mombin (Spondias mombin L.) is a good example. This fruit contains antioxidants, phenolic compounds such as flavonoids, phenolic acids, anthocyanins, carotenoids, and also vitamins A and C. Thus, this study aimed to characterize and quantify the yellow mombin edible peel, in order to direct the process of extraction of carotenoids by enzymatic maceration and then determine the best condition, through an experimental design, and also to evaluate the influence of physical and physico-chemical factors on enzymatic maceration of the yellow mombin edible peel, and finally performing enzymatic maceration in the the yellow mombin edible peel in a batch reactor and obtain a product powder through spray drying. The yellow mombin edible peel presented himself as a good source of carotenoids, where the best condition for recovery of carotenoids was using 300 µL of the Pectinex enzymatic complex XXL during 3 hours of incubation, reaching the level of 120.94 µg/g. Among the physical and physico-chemical factors, the use of enzyme preparations of cellulolytics status with the pectinolytic preparations for the recovery of carotenoids yellow mombin edible peel was not efficient, and adjusting the pH to neutrality (pH 6.0) before starting maceration proved efficient for a greater recovery of carotenoids, that in the laboratory level. The amount of water added in the process does not alter the recovery of carotenoids, used in proportions skin: water of 1: 2, 1: 3 or 1: 4. The use of ultrasound associated with enzymatic maceration worked at the laboratory scale. The use of batch reactor was technically feasible especially for the improvement of the conditions of homogenization of the mixture, which in turn led to obtaining higher levels of carotenoids recovered in the aqueous phase, not being necessary to adjust the pH of the reaction environment. Spray drying was possible being necessary suitability of the factors that influence drying to find the best condition necessary.